Men's Perceptions of an Acquaintance Rape: The Role of Relationship Length, Victim Resistance, and Gender Role Attitudes. (August 2015) - Angelone, D. J.; Mitchell, Damon; Grossi, Laura
Sexual aggression is a persistent and prevalent issue in the United States, which often results in a number of psychological, emotional, and physical consequences for victims. The current study examined whether the length of relationship between the victim and perpetrator, level of victim resistance, and observers' gender role attitudes play a role in observers' perceptions of an alleged sexual assault. Participants included 297 male college students from a public university in the Northeastern United States. Contrary to hypotheses, there were no significant effects for length of relationship on participants' attributions. Relative to no resistance, verbal and physical strategies by the victim predicted higher levels of victim credibility, perpetrator culpability, and perpetrator guilt, as well as lower levels of victim culpability and perceived victim pleasure. Endorsement of traditional adversarial sex role beliefs and hostile sexist attitudes, as opposed to egalitarian attitudes, were associated with the attribution of less credibility to the victim, perceived victim trauma, perpetrator culpability, perpetrator guilt, and shorter recommended prison sentences, as well as greater victim culpability and perceived victim pleasure. Laypersons' perceptions of sexual assault merit further study, as they are relevant to juror decision making and third party responses to sexual victimization (e.g., peer support for victim) and can contribute to the secondary victimization and recovery of survivors of sexual assault.